The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2478/v10255-012-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Measured by Age Reader in a Group of Patients with Obesity

Abstract: Background and Aim: Skin autofluorescence (AF) is a method used to detect the accumulation of Advanced Glycation End Products (AGEs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…AGEs are glycated proteins, lipids, and nucleic acids that present with chronic exposure to hyperglycemia, inflammation, and oxidative stress [ 3 , 7 ]. AGEs are considered a marker of metabolic memory [ 5 , 8 ]. AGEs can accumulate in tissues through aging, dietary intake, and smoking.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…AGEs are glycated proteins, lipids, and nucleic acids that present with chronic exposure to hyperglycemia, inflammation, and oxidative stress [ 3 , 7 ]. AGEs are considered a marker of metabolic memory [ 5 , 8 ]. AGEs can accumulate in tissues through aging, dietary intake, and smoking.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between micro-macrovascular complications and skin autofluorescence in patients with diabetes mellitus, renal failure, and cardiac diseases has been previously investigated [ 8 , 9 , 11 , 12 ], and SAF is an independent predictor of long-term cardiovascular complications. However, limited studies reported AGEs levels [ 13 15 ] or SAF [ 5 , 16 ] in patients with obesity. Body mass index (BMI) was found to be inversely correlated with SAF in patients with obesity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations